Attitudes and Knowledge About Donation in Catalonia. (July 2018) - Twose, Jorge; Arcos, Emma; Valles, Roser; Tort, Jaume
Abstract : Introduction: The Catalan Transplant Organization (OCATT) is the public organism of the Catalan Government responsible for planning, ordering, coordinating and assessing all the activities related to donation and transplantation of organs, tissues and cells in Catalonia since 1984. The objective of this study was to describe the attitudes and knowledge about donation in a representative survey in Catalonia in 2016. Methods: Data were obtained from the Health Survey of Catalonia (ESCA), a personal interview about health self-perception, lifestyle or use of health services, carried out to a representative sample of 2500 Catalan people. The survey introduced, during the first six months of 2016, seven questions intended to assess the attitudes and knowledge about organ donation. We collected 1, 750 surveys (people over 17 years old and not institutionalized) with information about donation. Questions were related with personnel situation about donation, Reasons for to be or not to be donor, shared donor decision, or knowledge about how to be a donor. From these questions we extract information about favourable attitude, effective donation and knowledge. We analysed this items according to some sociodemographic variables and we have also analyzed this data through a multivariate analysis using logistic regression. All the analyses were performed with SPSS 18. Results: In Catalonia, 80% of people were in favor of donation. We observed some significance differences according sex, age group, level of studies, self-perception health or country origin. Solidarity and altruism is the main reason (90.8%) for to be donor in people in favor of donation. Meanwhile 38% of people not in favor of donation don't know or don't say the reason, followed by the reason they thought their organs were not valid (15.2%). 36.7% of respondents shared with their relatives their own decision about to be donor, but only 1.5% have the donor card. 46% of people would donate the organs without knowing the opinion of deceased person, 87% would respect the decision of deceased person and 70% didn't know how to become a donor, with significant differences according some sociodemographic variables. Conclusion: Although in Catalonia the percentage of people in favor of donation is very high, the donor rate is near to 42 donors per million of population and the percentage of family refusals (15%) is lower than in other countries, campaigns of donation and transplantation promotion must be carried out in the future, if we want to increase our results even more. ESCA professionals. Figure. No caption available. Figure. No caption available. Figure. No caption available.